Determination of Urinary Calcium/Creatinine Ratio in a Spot Sample of Urine For Early Prediction of Pre-Eclampsia - Moni, SY; Ahmed, KM; Siddika, F; Habib, A; Ara, N; Rahman, MH (Bangladesh Medical Journal, 2014)
Based on the fact that urinary hypocalciuria in pre-eclampsia this study was designed to determine the predictive value of calcium to creatinine ratio in a spot urine sample in second trimester of pregnancy. The calcium to creatinine ratio Calcium/creatinine ratio has been considered for early detection of pre-eclamptic toxaemia (PET). So for the diagnosis of PET we try to investigate the relation of urinary calcium, urinary creatinine, urinary calcium/creatinine ratio. For this purpose total number of 60 healthy gravid and clinically suspected PET women of 20-28 weeks of pregnancy having age ranged from, 17-39 years were selected. On these 30 healthy pregnant women urinary calcium/creatinine ratio was within normal range and On the other hand urinary calcium/creatinine ratio in PET women was significantly decreased on the clinically diagnosed 30 PET women. These observations suggest that low calcium/creatinine ratio help in early prediction of PET .The result expressed by receiver operator curve analytic tecnique. Using the receiver operator curve a cut off level of 0.225 the calcium to creatinine ratio was chosen for prediction of PET. Twenty Two out of 30 woman had a calcium/creatinine ratio equal or less than 0.225. Thirty who had remained normotensive 13 had calcium/creatinine ratio equal or less than 0.225. This level thus yielded a 75% sensitivity and 65% specificity. Positive and negative predictive values 68.2% and 72.2% were calculated respectively, at this cut-off point. In conclusion a spot single urine sample calcium/creatinine ratio may be an effective method for screening pregnant women for detection of pre-eclampsia. DOI: http://dx.doi.org/10.3329/bmj.v41i2.18796 Bangladesh Medical Journal 2012 Vol. 41 No. 2: 20-22